Complaints Mechanisms in Institutions for Execution of Institutional Educational Measures and Juvenile Detention - Banić, Milena (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
The paper presents the complaint mechanisms that are available to minors deprived of liberty in institutions for the execution of institutional educational measures and juvenile detention. The paper presents the child’s right to appeal in the juvenile justice system by presenting the international and domestic legal framework and complaint mechanisms available to minors under the legislation of the Republic of Serbia in case of violation of their rights in the institutions for the execution of criminal sanctions. Special consideration is given to particular elements of complaint mechanisms: accessibility, child-sensitivity, safety and effectiveness. Implementation of the complaints mechanisms in institutions for the execution of institutional educational measures and juvenile detention is also considered. After all considerations, this paper provides recommendations for improving the complaint mechanisms as a necessary step in the realisation and protection of the rights of children deprived of their liberty.